Tafsir of Harmony:Efforts to Grow Multicultural Awareness - Tri Wahyudi Ramdhan; Saifuddin Saifuddin; Junaidi Junaidi (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2021)
This study will discuss Qur'anic verses that include messages of